Tax incentives and capital structure choice: Evidence from Germany - Thomas Hartmann-Wendels; Ingrid Stein; Alwin Stöter (Deutsche Bundesbank, 2012)
This paper provides new evidence that taxes affect capital structure choice, using a unique and comprehensive panel data set which covers 86,173 German non-financial firms over the years 1973-2008. Following the Graham methodology to simulate marginal tax rates, we find a statistically and economically significant positive relationship between the marginal tax benefit of debt (net and gross of investor taxes) and the debt ratio. A 10% increase in the net (gross) marginal tax benefit of debt causes a 1.5% (1.6%) increase in the debt ratio, ceteris paribus. The results are robust to various specifications like using changes in debt or debt to capital ratios. A significantly positive effect of taxes on the debt ratio can also be identified in a partial adjustment model.
Keywords: G32; H20; 330; debt; capital structure; marginal tax rate; corporate taxes; personal taxes